2015
DOI: 10.1016/j.concog.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Love is the triumph of the imagination: Daydreams about significant others are associated with increased happiness, love and connection

Abstract: Social relationships and interactions contribute to daily emotional well-being. The emotional benefits that come from engaging with others are known to arise from real events, but do they also come from the imagination during daydreaming activity? Using experience sampling methodology with 101 participants, we obtained 371 reports of naturally occurring daydreams with social and non-social content and self-reported feelings before and after daydreaming. Social, but not non-social, daydreams were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 63 publications
2
44
0
Order By: Relevance
“…For example, similar trait and state results have been obtained in the domain of event related potentials (e.g. Barron et al , 2011; Baird et al , 2014) and mood (Smallwood and O'Connor, 2011; Poerio et al , 2013, 2015). Other work also highlights the overlap between task-based and intrinsic functional connectivity (Smith et al , 2009; Krieger-Redwood et al , 2016).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, similar trait and state results have been obtained in the domain of event related potentials (e.g. Barron et al , 2011; Baird et al , 2014) and mood (Smallwood and O'Connor, 2011; Poerio et al , 2013, 2015). Other work also highlights the overlap between task-based and intrinsic functional connectivity (Smith et al , 2009; Krieger-Redwood et al , 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Our capacity for self-generated thought allows us to think about people and places that are not in the immediate environment, a process hypothesized to depend on retrieving internally stored representations that capture memories of past episodes and conceptual knowledge (Smallwood et al , 2016). These unconstrained experiences can have beneficial effects, including creativity (Baird et al , 2012; Smeekens and Kane, 2016), the alleviation of loneliness (Poerio et al , 2015, 2016a), psycho-social adaptation (Poerio et al , 2016b), and the refinement of goals (Medea et al , 2016). Despite these benefits of mind-wandering, the experience can also derail performance on concurrent tasks (McVay and Kane, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…By sampling naturally occurring daydreams, we have shown that social daydreaming can represent a means of achieving feelings of social connection, serving immediate socio-emotional regulation goals (Poerio, Totterdell, Emerson, & Miles, 2015b). Social (but not non-social) daydreams about close others had an immediate socio-emotional benefit by promoting positive social feelings of love and connection.…”
Section: Social Daydreaming and Adaptive Socio-emotional Outcomesmentioning
confidence: 96%
“…Although we may meditate alone, our meditation carries the traces from our teacher [4]. The thoughts that arise during meditation are mostly social, about others and our relationships, one is never alone [5]. So practicing mindfulness enhances our own awareness of our relatedness and interdependence, and as such will influence the way we relate to others.…”
Section: Relational Mindfulnessmentioning
confidence: 99%